FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MULTINASIONAL DI INDONESIA - farah Margaretha; Lina Sari (Media Riset Bisnis & Manajemen, 2005)
The purpose of this research is to find out the determinants of capital structure on multinational companies in Indonesia. The data are collected from 11 multinational companies in Indonesia which are listed in Jakarta Stock Exchange and have been selected by using testing hypothesis method. The sample are classified base on firm size, industry type and ownership control. This research uses simple linear regression and multiple linear regressions as the analysis method. The statistic test find out that the independent variables, which are firm size and ownership control, have an influence on capital structure. However, industry type has no influence on capital structure. Another result from this research is firm size, industry type and ownership control have an influence on capital structure simultaneously.